Renal Scintigraphy in Combination with Intravenous Pyelogram for the Diagnosis of Nephroptosis - Wang, Jiaqiong; Standiford, Taylor; Pryor, Jessica; Chao, Brian; Eun, Daniel D; Li, Yi; Meinel, Maria; Dadparvar, Simindokht; Yu, Jian Q (Archives of Clinical and Medical Case Reports, 2024)
Nephroptosis is defined as kidney descent more than 2 vertebral bodies (or >5 cm) during a position change from supine to upright. The current gold diagnostic standard is visual descent seen on intravenous pyelograms (IVP), which is limited to anatomical change. Renal scintigraphy would complement IVP to make the diagnosis of nephroptosis, and facilitate the evaluation of renal function. We report a series of 5 patients suspicious of nephroptosis who were examined by both IVP and renal scintigraphy with Tc-99m diethylenetriaminepentaacetic acid (Tc-99m DTPA) in the supine and upright positions. Renal scintigraphy was performed with a Co-57 source marker to locate the anterior iliac crest. Three cases were consistent with nephroptosis on IVP, four cases were consistent with nephroptosis on renogram. One case was consistent with nephroptosis on renogram but missed on IVP. One case was negative on both IVP and renogram. Some nephroptosis cases demonstrated decrease in calculated split renal function in the upright position. Renal scintigraphy is a valuable tool in the evaluation of nephroptosis. Renal scintigraphy can provide location information similar to IVP, and complementary functional information, which may aid urologists in confirming the diagnosis and selecting patients for nephropexy.